2021
DOI: 10.30682/tema0701b
|View full text |Cite
|
Sign up to set email alerts
|

Representation and knowledge of historic construction: HBIM for structural use in the case of Villa Palma-Guazzaroni in Terni

Abstract: A validated method for the digital representation of historic construction through HBIM permits assessment of compliance with workmanlike practices and structural performance. The construction of an appropriate model is closely linked to survey methodology, to the integrated application of multiple techniques of direct and indirect survey and non-destructive tests. The paper specifically deals with the complementarity between photogrammetry based on UAV (Unmanned Aerial Vehicles) with TLS (Terrestrial Laser Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The possibilities offered by HBIM in the field of cultural heritage are numerous. While these informative models guarantee and improve access to the data acquired in the survey processes, they also simplify the quantitative analyses useful for identifying conservation and management strategies for the historic built (Doria et al, 2018;Currà et al, 2021), thanks to the interoperability between different software guaranteed by the open format IFC (Industry Foundation Classes) (BuildingSMART, 2022;Gerbino et al, 2021). Based on these assumptions, a detailed digital model of the structural aggregate "La Giudea" was implemented in a parametric environment, in order to manage the information resulting from the knowledge process, document the current state, analyse the structural behaviour and identify the actions to be implemented from the conservation perspective.…”
Section: Methodsmentioning
confidence: 99%
“…The possibilities offered by HBIM in the field of cultural heritage are numerous. While these informative models guarantee and improve access to the data acquired in the survey processes, they also simplify the quantitative analyses useful for identifying conservation and management strategies for the historic built (Doria et al, 2018;Currà et al, 2021), thanks to the interoperability between different software guaranteed by the open format IFC (Industry Foundation Classes) (BuildingSMART, 2022;Gerbino et al, 2021). Based on these assumptions, a detailed digital model of the structural aggregate "La Giudea" was implemented in a parametric environment, in order to manage the information resulting from the knowledge process, document the current state, analyse the structural behaviour and identify the actions to be implemented from the conservation perspective.…”
Section: Methodsmentioning
confidence: 99%
“…Employing natural science analyses was principal, especially dendrochronology for dating elements of castle and tower roof truss. The AR-CHICAD images were used, and proficiency in historic building projecting was utilized to mediate obtained knowledge of the structure [18].…”
Section: Methodsmentioning
confidence: 99%
“…The problems of modeling, both informative and geometric, of the built heritage are obviously linked both to the complex system of historical-constructive knowledge, on the basis of manuals and documentary sources, and so not representative for typical software libraries [30], and by the constructional specificities and the evolution over time of the building object, such as, for example, the irregularities in the realization and the manifested degradation. These two specific areas of HBIM pose the greatest challenge of using the BIM tools and process, wherein the standardization logic typical of contemporary construction adapts with some problems to the unicum represented by the individual buildings of the built heritage [31,32].…”
Section: Bim and Palimpsestsmentioning
confidence: 99%
“…Deformations and irregularities of the case study have been reported with an integrated digital survey with multi-source and multi-resolution 3D imaging techniques [32]. For this reason, structure from motion (SfM) based on two image-based modelling (IBM) methods were used to recover 3D information in form of dense point cloud from images [60].…”
Section: From the Integrated Survey To Photogrammetric Reconstruction (Landscape To Building)mentioning
confidence: 99%